1989
DOI: 10.1007/bf01012380
|View full text |Cite
|
Sign up to set email alerts
|

Secondary attraction and field activity of beetle-produced volatiles inDendroctonus terebrans

Abstract: Controlled infestation ofDendroctonus terebrans (Olivier) on bolts of slash pine,Pinus ellionii Engelm. var.elliottii, elicited greater attraction of wild conspecifics than uninfested bolts. Secondary attraction was not apparent, however, to standing slash pines that had received volunteer attacks, when compared with attraction to unattacked but susceptible trees. Hindguts from in-flight or attacking femaleD. terebrans contained frontalin, and those from in-flight or attacking males containedexo-brevicomin.Tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…Given the very small amounts of exo-brevicomin present in D. frontalis, the compound may not function as a pheromone per se, but the beetles' responses may reflect interspecific interactions with species that produce larger quantities. As previously mentioned, the black turpentine beetle D. terebrans releases exo-brevicomin as part of its pheromone Phillips et al, 1989), and D. frontalis cross-attraction to exo-brevicomin from this species could aid it in locating and exploiting lightning struck or other compromised hosts discovered by D. terebrans (Smith et al, 1990). Similar cross-attraction may occur in the sympatric zone of D. frontalis and D. brevicomis located in the southwestern United States, as the latter produces exo-brevicomin as an important component of its aggregation pheromone and the two species frequently cohabit the same host trees (Davis and Hofstetter, 2009;Hofstetter et al, 2008;Pureswaran et al, 2008a).…”
Section: Endo-brevicominmentioning
confidence: 86%
See 1 more Smart Citation
“…Given the very small amounts of exo-brevicomin present in D. frontalis, the compound may not function as a pheromone per se, but the beetles' responses may reflect interspecific interactions with species that produce larger quantities. As previously mentioned, the black turpentine beetle D. terebrans releases exo-brevicomin as part of its pheromone Phillips et al, 1989), and D. frontalis cross-attraction to exo-brevicomin from this species could aid it in locating and exploiting lightning struck or other compromised hosts discovered by D. terebrans (Smith et al, 1990). Similar cross-attraction may occur in the sympatric zone of D. frontalis and D. brevicomis located in the southwestern United States, as the latter produces exo-brevicomin as an important component of its aggregation pheromone and the two species frequently cohabit the same host trees (Davis and Hofstetter, 2009;Hofstetter et al, 2008;Pureswaran et al, 2008a).…”
Section: Endo-brevicominmentioning
confidence: 86%
“…However, as suggested by Hodges and Pickard (1971), D. terebrans could play a role in attracting D. frontalis to trees struck by lightning or receiving other types of injury. Dendroctonus terebrans is typically the first bark beetle species to arrive on a lightning-struck tree (Hodges and Pickard, 1971), whereas attacking D. terebrans pairs generate all components of the D. frontalis aggregation attractant Phillips et al, 1989): frontalin and trans-verbenol (by females), both endo-and exo-isomers of brevicomin (by males), and resin odors from the damaged host tissue. Thus, as suggested by Payne et al (1987), a kairomonal response by D. frontalis to trees attacked by D. terebrans could assist the former in locating lightning-struck host trees.…”
Section: Host Location By Pioneering D Frontalismentioning
confidence: 99%
“…It may be that new volatiles produced by males in the paired treatment affect male attraction and that the new volatiles negate the attractive effect of "frontalin" for male. Phillips et al (1989) also reported a pheromone named brevicomin in D. terebrans, which was contained in the hindgut of in-ßight or attacking males. The similarity between V p and V & for males may cast doubt on the claim that red turpentine beetles are monogamous; however, using stridulation, males can determineÑat least from a short distanceÑwhether the hole is occupied by other red turpentine beetles, as McGhehey showed.…”
Section: Sexmentioning
confidence: 94%
“…Other female bark beetlesÕ hindgut or frass have been reported to contain such sex pheromones or attractants, namely frontalin (Renwick andVité 1969, Phillips et al 1989) and brevicomin (Silverstein et al 1968). Phillips et al (1989) proved that the pheromone frontalin was contained in the hindguts of in-ßight or attacking females of the black turpentine beetle D. terebrans, which is closely related to D. valens and was very attractive to male D. terebrans in Þeld-trapping experiments.…”
Section: August 2006mentioning
confidence: 96%
“…While numerous studies have examined the chemical ecology of sibling species D. valens and D. terebrans Olivier (Phillips et al, 1989;Hobson et al, 1993;Sun et al, 2004;Zhang and Sun, 2006;Erbilgin et al, 2007;Shi and Sun, 2010), the semiochemistry of D. rhizophagus has not previously been investigated. We, therefore, performed studies on D. rhizophagus to identify compounds of the host tree and the beetle that might mediate host and mate location for this species and possibly provide chemical baits for its management.…”
Section: Introductionmentioning
confidence: 99%